Design and Development of a 6-Digit Microcontroller Based Nuclear Counting System (International Journal of Scientific Research and Management (IJSRM), 2013)
6-digit microcontroller based nuclear counting system has been described in this paper although it is possible to extension upto 12-digit or so on. As the system is independent of nominal memory mapping and large pin configuration. For the ease of testing and simplicity, it has been built upto 6-digit. The system includes PIC microcontroller as the key device that avoids lots of conventional analog circuitry. Therefore, the system is compact, low cost, least noise, better accuracy .The system has been designed with GM detector and locally developed high voltage power supply. MPlab, assembly language program development environment, controls the operation of the designed system. The system has been tested with standard pulser from accredited manufacturer for its performance verification.